2006
DOI: 10.1007/s11676-006-0078-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urea-N fertilizer dosage supplemented with Ipil-Ipil tree litter on yield of rice and insect prevalence

Abstract: The present study was undertaken to determine the effects of different levels of urea-N fertilizer in addition to ipil-ipil tree litter on yield of rice and insect prevalence. The field study was conducted at the Agroforestry Field Laboratory, Bangladesh Agricultural University, Mymensingh during July-December 2004. The treatments included 0, 90, 180, and 270 kg urea per hectare. All four treatments received five tons ipil-ipil tree litter per hectare. The experiment was laid out in a randomized complete block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In the present study, farmers reported ten ways of reducing pesticides. Farmers stressed the importance of using balanced doses of fertilizers and this is in agreement with previous studies that have suggested applying organic materials mixed with nitrogen fertilizer to minimize pest prevalence in the rice field 50, 51. Pest monitoring and removal of egg mass were also named as alternative ways of reducing pesticides by the farmers.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, farmers reported ten ways of reducing pesticides. Farmers stressed the importance of using balanced doses of fertilizers and this is in agreement with previous studies that have suggested applying organic materials mixed with nitrogen fertilizer to minimize pest prevalence in the rice field 50, 51. Pest monitoring and removal of egg mass were also named as alternative ways of reducing pesticides by the farmers.…”
Section: Discussionsupporting
confidence: 83%
“…According to Pennazio [ 33 ], the development of mineral nutrition of plants began between the 17th and 18th centuries. The patterns of mineral fertilizer applications in different cropping systems, as well as their impact on the environment, continue to nourish the debate globally [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. However, the increase in food demands due to the rapid increase in the global population has shown the necessity to enhance the productivity of food crops.…”
Section: Historical Use Of Nitrogen and N-rich Fertilizers In Agricul...mentioning
confidence: 99%